NILAI-NILAI PENDIDIKAN ISLAM DALAM PERSPEKTIF KH. NUR HASANUDIN - Muhsin Arif; Azhar haq; Ika Anggraheni (VICRATINA, 2019)
Religus education is fundamental, particularly moral part to be taught in early process of it. Morality is the key be smart intelectally, apriritualy and emotionally. It is the responsibility of parent, theacer, and community to provide Islamic values for the student. For that, there must be a strategy in delivering these values, some strategis that can be done to deliver religious values are example or moral, habituation, advice, punishment.